Big Data Utilization and Online Promotion Strategy Impacting Customer Satisfaction Through Digital Experience and Buying Decision West Java - Indra Surya Permana Permana; Ahmad Ngiliyun (Jurnal Bisnis dan Kewirausahaan, 2026)
This study examines the influence of big data utilization and online promotion strategy on customer satisfaction, digital experience, and buying decision in the context of digital consumers in West Java. A quantitative approach was employed using a survey method with 250 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that big data utilization and online promotion strategy significantly affect customer satisfaction. Furthermore, customer satisfaction has a significant impact on both digital experience and buying decision. The findings also reveal that big data utilization directly influences digital experience, while online promotion strategy directly affects buying decision. These results suggest the presence of both direct and indirect relationships, highlighting the mediating role of customer satisfaction. The study confirms that data-driven strategies and effective digital promotion are critical in enhancing customer perceptions and behavior. From a theoretical perspective, this research extends the concept of data-driven customer experience by integrating multiple outcome variables. Practically, the findings provide insights for businesses to optimize digital marketing strategies and improve customer engagement. Overall, this study contributes to a deeper understanding of digital marketing effectiveness in emerging markets.